A Contrastive Analysis of the Use of Prepositions in German and Indonesian - Hasmawati Hasmawati; Mantasiah R.; Yusri Yusri (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
This study aims to describe the implication of contrastive analysis in the mastery of prepositions in German and Indonesian by identifying the similarities and differences in terms of morphology, semantics and syntax. This study employed library research technique to collect data related to the use of prepositions in German and Indonesian. The results of analysis found that there are similarities and differences in using the prepositions in German and Indonesian. Based on the word structure or the morphological aspect, prepositions in German and Indonesian are divided into two: primary/pure/basic prepositions and secondary/derivative prepositions. In German and Indonesian, primary prepositions are single words, which are called prepositions with one case in German (Präpositionen mit festem Kasus). From the semantic point of view, German prepositions are divided into four types: 1) prepositions indicating locative relationship, 2) temporal relationship, 3) modal relationship, and 4) cause-effect relationship. In Indonesian, however, prepositions are divided into several types: 1) prepositions indicating location, 2) movement, 3) agents, 4) tools, 5) comparison, 6) a thing or problem, 8) effects, and 9) prepositions indicating purpose. In general, those prepositions have similar meanings with prepositions in German, but the formations are different because prepositions in German use one of the cases: accusative, dative or genitive